2014
DOI: 10.1111/mec.12948
|View full text |Cite
|
Sign up to set email alerts
|

Synechococcus: 3 billion years of global dominance

Abstract: Cyanobacteria are among the most important primary producers on the Earth. However, the evolutionary forces driving cyanobacterial species diversity remain largely enigmatic due to both their distinction from macro-organisms and an undersampling of sequenced genomes. Thus, we present a new genome of a Synechococcus-like cyanobacterium from a novel evolutionary lineage. Further, we analyse all existing 16S rRNA sequences and genomes of Synechococcus-like cyanobacteria. Chronograms showed extremely polyphyletic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 74 publications
5
70
0
Order By: Relevance
“…see Komárek 2010 for review of older works, afterwards e.g. Strunecký et al 2011;Komárek et al 2013;Komárková et al 2013;Dvořák et al 2014a). During the 19th Symposium of the International Society for Cyanophyte Research in 2013, 16 new genera were presented .…”
Section: Estimate Of the Total Cyanobacterial Biodiversitymentioning
confidence: 99%
See 1 more Smart Citation
“…see Komárek 2010 for review of older works, afterwards e.g. Strunecký et al 2011;Komárek et al 2013;Komárková et al 2013;Dvořák et al 2014a). During the 19th Symposium of the International Society for Cyanophyte Research in 2013, 16 new genera were presented .…”
Section: Estimate Of the Total Cyanobacterial Biodiversitymentioning
confidence: 99%
“…They also designed a concrete species definition based on the mentioned concept, which is suitable for cyanobacteria and may be used under the International Code of Botanical Nomenclature. It is probably the most widely accepted concept with cyanobacteria (according to the number of taxonomic papers using the concept under the Botanical Code), although sometimes not precisely followed (Siegesmund et al 2008;Perkerson et al 2011;Dvořák et al 2014a;Hašler et al 2012Hašler et al , 2014aOsorio-Santos et al 2014 and many others). The most important advantage of the monophyletic species concept is the general applicability to asexual organisms.…”
Section: Particular Problems Of Species Definitions and Concepts In Cmentioning
confidence: 99%
“…Such a polyphyly might be extreme. For instance, Dvořák et al (2014a) noted 12 lineages within the genus Synechococcus sensu lato, which suggest frequent convergence in cyanobacteria. What might be the reasons for such entangled evolutionary relationships?…”
Section: Introductionmentioning
confidence: 99%
“…What might be the reasons for such entangled evolutionary relationships? Dvořák et al (2014a) suggested that homologous recombination and horizontal gene transfer within local gene pools sensu Polz et al (2013) provide a space for convergence of phenotypes, and therefore an existence of polyphyletic groups.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Robertson et al (2001) found five polyphyletic lineages in the morphologically simple, coccoid genus Synechococcus. A more recent analysis by Dvořák et al (2014a) found 12 lineages in this same genus and proposed that cyanobacteria undergo serially convergent events due to genome dynamics through horizontal gene transfer and homologous recombination. These and similar findings provide support for splitting polyphyletic genera into smaller, monophyletic lineages and subsequently describing new taxa.…”
Section: Introductionmentioning
confidence: 99%